Hyperbaric oxygen promotes both the proliferation and chemosensitization of glioblastoma cells by inhibiting HIF1α/HIF2α-ABCG2 - Gong, Sheng; Wang, Pan; Liao, Bin; Zhao, Lu; Wu, Nan (Frontiers in Molecular Neuroscience, 2025)
IntroductionHyperbaric oxygen enhances glioma chemosensitivity, but the mechanism remains unclear. Hypoxia is common in gliomas, and as the main effector molecules of hypoxia, HIF1α and HIF2α promote the malignant progression by inhibiting cell apoptosis and maintaining stemness. ABCG2 is a marker protein of tumor stem cells and drug efflux transporter protein. This study aims to reveal the detailed mechanism of hyperbaric oxygen promote both proliferation and chemosensitization.MethodsUnder hyperbaric oxygen and hypoxic conditions, we investigated the differences in cell cycle, proliferation, apoptosis, LDH release, and the expression of proteins and mRNA. We also conducted studies on transcriptional regulation and performed in vivo experiments.ResultsIt revealed that under hypoxic conditions, HIF1α, HIF2α, and ABCG2 are highly expressed, and both HIF1α and HIF2α promote ABCG2 expression. After hyperbaric oxygen treatment, the expression of HIF1α, HIF2α, and ABCG2 decreased, both cell proliferation and chemosensitivity increased. After knocking out HIF1α and HIF2α, cell proliferation and chemosensitivity increased, but the expression of stem cell marker proteins decreased. ChIP-qPCR revealed that HIF1α and HIF2α target the ABCG2 promoter. Gain-and loss-of-function experiments suggested that ABCG2 can promote the expression of stem cell marker proteins, inhibit cell apoptosis, and promote tumor progression.ConclusionThis study confirmed that hyperbaric oxygen can inhibit ABCG2 expression through HIF1α and HIF2α, thereby promoting the proliferation and chemosensitization of gliomas.